2021
DOI: 10.1257/app.20190703
|View full text |Cite
|
Sign up to set email alerts
|

Minority Salience and Political Extremism

Abstract: We investigate how the salience of an ethnic minority affects the majority group’s voting behavior. We use the increased salience of Muslim communities during Ramadan as a natural experiment. Exploiting exogenous variation in the distance of election dates to Ramadan over the 1980–2013 period in Germany, our findings reveal an increased polarization. Vote shares for both right- and left-wing extremist parties increase in municipalities with mosques when an election takes place shortly after Ramadan. We use sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…For example, Enos (2014) shows that repeated exposure to Hispanics on Boston trains worsens White individuals' views on immigration. Colussi, Isphording and Pestel (2021) find that the salience of Muslim communities in Germany during Ramadan increases political polarization.…”
Section: Lebanon's Religious Conflictmentioning
confidence: 79%
“…For example, Enos (2014) shows that repeated exposure to Hispanics on Boston trains worsens White individuals' views on immigration. Colussi, Isphording and Pestel (2021) find that the salience of Muslim communities in Germany during Ramadan increases political polarization.…”
Section: Lebanon's Religious Conflictmentioning
confidence: 79%
“…Answer of the Federal government to a parliamentry query of the party Die Linke (far-left party). Data shared by Colussi et al (2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we obtain data on political attitudes in more recent times: the 2013 vote share of the far-right, anti-immigrant National Democratic Party (NPD) from the Federal Elections O ce (Bundeswahlleiter, 2020), and the frequency of marches organized by the far-right political groups between 2005 and 2012 from Kanol & Knoesel (2021). Third, we use attacks against mosques between 2001 and 2011 from Colussi et al (2021). Finally, we measure ethno-centrism of locals by combining antiimmigrant and anti-diversity attitudes from ALLBUS (pooling the survey years 2008, 2010, and 2012), 13 and an inverse measure for "openness" -a sub-dimension of the Big-5 personality traits associated with ethnocentrism from the SOEP.…”
Section: Measurementmentioning
confidence: 99%
“…Some recent papers have found evidence that higher immigration flows lead to stronger support for right-wing parties (see, for example, Barone et al, 2016;Halla et al, 2017;Dustmann et al, 2019;Brunner and Kuhn, 2018;Becker and Fetzer, 2016), while other work has found evidence going in the opposite direction (see Dill, 2013;Steinmayr, 2016). Colussi et al (2016) find that vote shares for both right-and left-wing extremist parties increase in German municipalities containing mosques when election dates are closer to the Ramadan period (a shock to the salience of the Muslim community). Alesina et al (2018b) experimentally find that priming subjects to think of immigration lowers support for redistribution.…”
Section: Introductionmentioning
confidence: 85%